2003
DOI: 10.1034/j.1600-0773.2003.920407.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressant Effects of Ambroxol and Erdosteine on Cytokine Synthesis, Granule Enzyme Release, and Free Radical Production in Rat Alveolar Macrophages Activated by Lipopolysaccharide

Abstract: The present study examined the effects of ambroxol and erdosteine, bronchial expectorants, on the cytokine synthesis, granule enzyme release, and free radical production in rat alveolar macrophages activated by lipopolysaccharide. Ambroxol and erdosteine significantly decreased the production of tumour necrosis factors-a, interleukin-1b, and interleukin-6 in alveolar macrophages activated by lipopolysaccharide. These drugs significantly reduced the production of superoxide anion, hydrogen peroxide, and nitric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
1
35
0
6
Order By: Relevance
“…Similarly, an erdosteine metabolite was reported to react with ROS, NO, and NO-derived peroxynitrite and exert both antioxidant and scavenging activities [46]. Moreover, erdosteine inhibits cytokine synthesis and free radical production in rat alveolar macrophages by effectively decomposing NO [47].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, an erdosteine metabolite was reported to react with ROS, NO, and NO-derived peroxynitrite and exert both antioxidant and scavenging activities [46]. Moreover, erdosteine inhibits cytokine synthesis and free radical production in rat alveolar macrophages by effectively decomposing NO [47].…”
Section: Discussionmentioning
confidence: 97%
“…Ambroxol has many biological actions on various cell types. Jang et al [27] reported that ambroxol significantly reduced the production of superoxide anion, hydrogen peroxide, and nitric oxide and the release of acid phosphatase and lysozyme in LPS-activated macrophages. Yang et al [20] reported that ambroxol transiently suppressed release of the cytokines TNFa, interferon g and IL-12 into airway fluid.…”
Section: Discussionmentioning
confidence: 98%
“…Jang et al [21] reported that erdosteine inhibited the synthesis of cytokines including tumor necrosis factor (TNF)-α, IL-1β, and IL-6, and free radical (superoxide, hydrogen peroxide) production in rat alveolar macrophages activated by LPS. They suggest that the inhibitory effect of erdosteine on inflammatory cytokine synthesis and ROS production contributes to the anti-inflammatory effect of erdosteine.…”
Section: Discussionmentioning
confidence: 99%